Research on Student Management Model of Higher Vocational Colleges Based on Cloud Platform - Yang Xu (ITM Web of Conferences, 2019)
This paper analyzes the current situation of higher vocational students and the problems existing in the management of higher vocational students, and puts forward the idea of making use of cloud computing technology to innovate the management of higher vocational students, that is, to construct an interactive system based on the educational cloud platform. To realize the interaction between teachers and students. The construction of student management model based on cloud platform is the requirement of information construction of student management and the reform of talent training mode in higher vocational colleges.